(Al, Ga)Ox Microwire Ensembles on Si Exhibiting Luminescence over the Entire Visible Wavelength Range. Issue 12 (26th September 2016) - Ishikawa, Fumitaro; Corfdir, Pierre; Jahn, Uwe; Brandt, Oliver
Abstract : The broad visible light emission observed for GaAs/(Al, Ga)O x core/shell microwires (μ‐wires) arises from recombination at F centers in the (Al, Ga)O x shells. These μ‐wires are promising structures for obtaining white‐light emission on a Si platform. To realize efficient white‐light emitters, it is essential to prevent the transfer of carriers to the GaAs core and the shell surface.